Plantas medicinais utilizadas no tratamento da obesidade: revisão sistemática de ensaios clínicos - Almeida, Fernando Henrique Oliveira de (2019)
Obesity is a complex disease with a multifactorial etiology. It is the second most common cause of preventable death after smoking. The increase in overweight and obesity in the world is evident in studies, with data from more than 19.2 million adults in 186 countries. Complementary and alternative therapies have been used for many years, but recently they are being used more and more around the world. Due to the high costs of synthetic drugs to control obesity and their adverse effects, the use of medicinal plants and herbal medicines has been gaining ground in weight control. The present work aimed to map scientific evidence about medicinal plants with therapeutic properties in the treatment of obesity and their efficacy and safety for the patient. To carry out the review, 292 articles were identified, of which after evaluation and literature, only 24 articles fit the inclusion criteria and were used in the systematic review. The results of this systematic review demonstrate the effectiveness of phytotherapy and medicinal plants for the treatment of obesity and metabolic syndrome, but it also demonstrated a great fragility concerning studies focused on patient safety. In the future, it becomes necessary to standardize studies focused on the efficacy and safety of medicinal plants and herbal medicines in obesity, in order to ensure that the product being used in therapy is of good quality, safe, with minimal side effects for the patient.